(untitled) (Fiep Bulletin - online, 2015)
This descriptive study had as general objective analyze the anxiety traits and anxiety state levels in Rhythmic Gymnastics athletes on specific situations of motor performance. Were subject, ten youth and adult athletes of the Maringá Paraná. Specifically, as a specific objective verified the anxiety trait and of anxiety state levels in different situations, observing the practice experience and comparing ages. As measure instrument was used the anxiety trait protocol (SCAT), and the anxiety state protocol (CSAI-2). The data regarding the anxiety traits was collected in training situation and the data about anxiety state during the competition situation. The data were collected in several moments through one year. The descriptive statistics was used for data analysis. The results demonstrated: the athletes related an important anxiety level that increased into competition; so much the level of anxiety trait was higher in the athletes with age between 15 to 18 years; the athletes with larger time of practice experience went the ones that they presented a better emotional stability. In conclusion: the anxiety influenced the rhythmic gymnastics athlete’s motor performance, demonstrating to be an intervening factor that should be controlled by professionals of the sport psychology.